ENHANCING DIABETES CARE: THE ROLE OF HEALTH ADMINISTRATION, HEALTH INFORMATICS, MEDICINE AND NURSING IN PATIENT EDUCATION AND SUPPORT - Saeed Rashed Mohammed Alyami, Faris Ali Mana Al Hider, Majed Manea Doman Al Yami, Yahya Hamad Alhaydar, Fares Manahussaen Aljafar, Mohsen Ahmad Albkri Mohammed Adel Alhaydar, Ali Fares Saleh Al Abbas, (Chelonian Research Foundation, 2022)
Background: Research indicates that improved health outcomes may result from a more structured approach to enhance diabetes care. We have to create an evidence-based design plan for the Chronic Disease Management like diabetes, which seeks to use clinical care approach and provide education, knowledge and support to patient through collaboration with health administration, health informa tics, physician and nurses to help diabetes patients and provide a good care as effectively as possible. Purpose: The purpose of this review is to illustrate the importance of health team members working together to provide excellent diabetes care management in general practice. This includes health administration, health informatics, physicians, and nurses. Method: Articles retrieved from pertinent databases utilizing search criteria linked to diabetes, diabetic care management, patient education, and support served as the foundation for the literature evaluation. Papers published in English from 2000 to September 2019 that were based on original research assessingform intervention in healthcare settings. Result: 18 articles was selected and reviewed based on inclusion criteria and discussing the various facets of diabetes care, including the accessibility of medications, diagnostic equipment and the role of medical professionals. Conclusion: Reducing the development of diabetes-related health problems can be achieved through the applying of a multidisciplinary team approach involving the diabetic patient their primary caregiver, and additional medical specialists by promoting a productive and informative interaction between the patient and the care team. However, there is still a great deal ofwork to be done to address the deficiencies in diabetes care throughout the health system. Tofigure out how to incorporate diabetes care into the healthcare system, more research is also required. Keywords: Health informatics, Diabetes care; patient education, Health administration, knowledge, chronic disease management.